PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERBASIS MODEL PEMBELAJARAN CORE (CONNECTING, ORGANIZING, REFLECTING, EXTENDING) PADA MATERI KESETIMBANGAN ION DAN PH LARUTAN PENYANGGA UNTUK KELAS XI SMA/MA - Ginting, Emmia Yulita; Holiwarni, Betty; Erviyenni, Erviyenni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The objective of this research was to develop the student?s worksheets based on the CORE (Connecting, Organizing, Reflecting, Extending) learning model in the subject of Equilibrium Ion and pH of Buffer Solution. The type of research was Research and Development method with the 4-D development model which includes Define, Design, Develop, Dissemminate. The research was only carried out at the Develop step, which was a limited trial section. The study was conducted at the FKIP of the Riau University. The object of the research was the student?s worksheets based on the CORE learning model. The data analysis technique used in the study was descriptive statistical analysis by calculating the percentage of validation?s score. The average validation results of student?s worksheet by 3 lecturers as the expert were 88.99% with the valid category and had fulfilled the aspects of content eligibility, the characteristics of the CORE Learning Model in the subject of Equilibrium Ion and pH of Buffer Solution, language, presentation and graphics. The results of the assessment of the limited trial student?s worksheet by 2 teachers as validator users and 11 students as users obtained percentage of 94.64% and 86.85% which were on positive criteria.Key Words: Student?s Woorksheet, CORE learning models, Equilibrium Ion and pH of Buffer Solution